Knowledge about syphilis among patients of two basic health units in the state of São Paulo - Pires, Antônio Lourenço Neto; Iembo, Tatiane; Silva, Melissa Carol da (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: The number of new cases of syphilis remains high in Brazil, which may be related to the influence of demographic factors on the sexual behavior of individuals and the lack of basic knowledge about the disease, which is very important for prevention and treatment. Objective: To evaluate the knowledge about syphilis in a sample of patients from Basic Health Units (BHUs) in the city of São José do Rio Preto, São Paulo. Methods: This is a crosssectional descriptive study. We assessed the perception of the participants about the disease through a questionnaire with objective questions. We analyzed the results using descriptive statistics. Results: We interviewed 193 patients – 95 in BHU1 and 98 in BHU2. With regard to syphilis, 65% of participants from the two BHUs claimed to know about the disease, and even though most have answered correctly about its means of transmission, more than 11% of BHU1 patients and almost 5% of those from BHU2 chose options not related to intercourse. Almost half of the patients did not know the main symptom in early syphilis. More than 50% of patients never talked to their sexual partner about this disease. 80% of patients from BHU1 and 95% from BHU2 were not tested for syphilis in the past 12 months. Conclusion: The patients’ lack of knowledge about syphilis was evident in both BHU1 and 2, which is a real concern due to the severity this disease can reach. The results reinforce that health actions are necessary to prevent syphilis in the districts surveyed.